Enhanced lipid metabolism induces the sensitivity of dormant cancer cells to 5-aminolevulinic acid-based photodynamic therapy - Taku Nakayama (Nature Portfolio, 2021)
Abstract Cancer can develop into a recurrent metastatic disease with latency periods of years to decades. Dormant cancer cells, which represent a major cause of recurrent cancer, are relatively insensitive to most chemotherapeutic drugs and radiation. We previously demonstrated that cancer cells exhibited dormancy in a cell density-dependent manner. Dormant cancer cells exhibited increased porphyrin metabolism and sensitivity to 5-aminolevulinic acid-based photodynamic therapy (ALA-PDT). However, the metabolic changes in dormant cancer cells or the factors that enhance porphyrin metabolism have not been fully clarified. In this study, we revealed that lipid metabolism was increased in dormant cancer cells, leading to ALA-PDT sensitivity. We performed microarray analysis in non-dormant and dormant cancer cells and revealed that lipid metabolism was remarkably enhanced in dormant cancer cells. In addition, triacsin C, a potent inhibitor of acyl-CoA synthetases (ACSs), reduced protoporphyrin IX (PpIX) accumulation and decreased ALA-PDT sensitivity. We demonstrated that lipid metabolism including ACS expression was positively associated with PpIX accumulation. This research suggested that the enhancement of lipid metabolism in cancer cells induces PpIX accumulation and ALA-PDT sensitivity.